Structure of the Collision Zone Between the Nazca Ridge and the Peruvian Convergent Margin: Geodynamic and Seismotectonic Implications. Issue 9 (11th September 2019) - Contreras‐Reyes, E.; Muñoz‐Linford, P.; Cortés‐Rivas, V.; Bello‐González, J. P.; Ruiz, J. A.; Krabbenhoeft, A.
Abstract: We study the structure and tectonics of the collision zone between the Nazca Ridge (NR) and the Peruvian margin constrained by seismic, gravimetric, bathymetric, and natural seismological data. The NR was formed in an on‐ridge setting, and it is characterized by a smooth and broad shallow seafloor (swell) with an estimated buoyancy flux of ~7 Mg/s. The seismic results show that the NR hosts an oceanic lower crust 10–14 km thick with velocities of 7.2–7.5 km/s suggesting intrusion of magmatic material from the hot spot plume to the oceanic plate. Our results show evidence for subduction erosion in the frontal part of the margin likely enhanced by the collision of the NR. The ridge‐trench collision zone correlates with the presence of a prominent normal scarp, a narrow continental slope, and (uplifted) shelf. In contrast, adjacent of the collision zone, the slope does not present a topographic scarp and the continental slope and shelf become wider and deeper. Geophysical and geodetic evidence indicate that the collision zone is characterized by low seismic coupling at the plate interface. This is consistent with vigorous subduction erosion enhanced by the subducting NR causing abrasion and increase of fluid pore pressure at the interplate contact. Furthermore, the NR has behaved as a barrier for rupture propagation of megathrust earthquakes (e.g., 1746 Mw 8.6 and 1942 Mw 8.1 events). In contrast, for moderate earthquakes (e.g., 1996 Mw 7.7 and 2011 Mw 6.9 events), the NR has behaved as a seismic asperity nucleating at depths >20 km. Key Points: The Nazca Ridge hosts an overthickened lower crust (10–14 km) formed in an on‐ridge setting (hot spot plume near a spreading center) The Nazca Ridge correlates with a prominent continental slope scarp bounded by a narrow and uplifted continental shelf The Nazca Ridge has behaved as a seismic asperity for moderate earthquakes (e.g., 1996 Mw 7.7 and 2011 Mw 6.9) nucleating at depths >20 km